7
$\begingroup$

I have the matrix:

$$A=\begin {pmatrix} 0 &-1\\ 1 & 0\\ \end{pmatrix}$$ And I want to try to calculate its exponential using this formula $$\ e^{M} = \sum_{k=0}^\infty \frac{1}{k!}\ M^{k}\\$$

I have worked out that $$A^{2} = -I$$ $$A^{3}=-A$$ and $$A^{4}=I$$ where I is the identity matrix. I have then tried to use the fact that the sum will cycle through these matrices to separate the sum and then recombine it into one matrix. However what I get out cannot easily be expressed as a sum. Any help would be greatly appreciated!

$\endgroup$
  • 2
    $\begingroup$ You should get a numerical series times $I$ plus a numerical series times $A$. Both these series of numbers should look familiar... $\endgroup$ – Lord Shark the Unknown Mar 1 '18 at 18:47
  • $\begingroup$ Collect the terms in $A$ and $I$ and factor those matrices out. Do you recognize the resulting series? $\endgroup$ – amd Mar 1 '18 at 18:47
10
$\begingroup$

You have\begin{align}e^A&=\begin{pmatrix}1&0\\0&1\end{pmatrix}+\begin{pmatrix}0&-1\\1&0\end{pmatrix}+\frac12\begin{pmatrix}-1&0\\0&-1\end{pmatrix}+\frac1{3!}\begin{pmatrix}0&1\\-1&0\end{pmatrix}+\frac1{4!}\begin{pmatrix}1&0\\0&1\end{pmatrix}+\cdots\\&=\begin{pmatrix}1-\frac1{2!}+\frac1{4!}-\cdots&-1+\frac1{3!}-\frac1{5!}+\cdots\\1-\frac1{3!}+\frac1{5!}-\cdots&1-\frac1{2!}+\frac1{4!}-\cdots\end{pmatrix}\\&=\begin{pmatrix}\cos(1)&-\sin(1)\\\sin(1)&\cos(1)\end{pmatrix}.\end{align}

$\endgroup$
15
$\begingroup$

Split the sum into odd and even terms

\begin{eqnarray} e^A &=& \sum_{k=0}^{+\infty}\frac{A^{2k}}{(2k)!} + \sum_{k=0}^{+\infty}\frac{A^{2k+1}}{(2k+1)!} \\ &=& \sum_{k=0}\frac{(-1)^{k}}{(2k)!}I + \sum_{k=0}^{+\infty}\frac{(-1)^{k}}{(2k+1)!}A \\ &=& \cos(1) I + \sin(1)A \\ \end{eqnarray}

$\endgroup$
  • 1
    $\begingroup$ +1 elegant answer..Cant you consider I as $A^0$ ? $\endgroup$ – Isham Mar 1 '18 at 19:04
  • 1
    $\begingroup$ @Isham Thanks for the suggestion, you can indeed. I already fixed it $\endgroup$ – caverac Mar 1 '18 at 19:06
5
$\begingroup$

A sketch:

First consider this matrix as a matrix in $\mathcal M_2(\mathbf C)$, and diagonalise it. Its characteristic polynomial is $\lambda^2+1$, so the eigenvalues are $i,-i$. One finds corresponding eigenvectors: $e_1=(1,1)$ and $e_2=(1,i)$. In this basis, the diagonal matrix $D$ of eigenvalues has exponential: $$\exp D=\exp\begin{pmatrix}\mathrm e^i &0\\0&\mathrm e^{-i}\end{pmatrix}.$$ Now, the change of basis matrix from the canonical basis to basis $(e_1,e_2)$ and its inverse are $$P=\begin{pmatrix}i&1\\1&i\end{pmatrix},\quad P^{-1}=\tfrac12\begin{pmatrix}-i&1\\1&-i\end{pmatrix}.$$ Also, we know that $D=P^{-1}AP,\quad \text{so }\enspace A=PDP^{-1}$and $$\exp A=P\exp(D)P^{-1}=\text{ (some computation) }= \begin{pmatrix}\cos 1&-\sin 1\\\sin 1&\cos 1\end{pmatrix}$$ i.e. the matrix of rotation by 1 rad.

$\endgroup$
2
$\begingroup$

It is straightforward using the formula above to check that $t \mapsto e^{At}$ satisfies the ODE $\dot{X} = AX$, $X(0) = I$. We want to compute $X(1) = e^A$.

Note that $\ddot{X} = -X$, so each entry has the general solution $t \mapsto a \cos t + b \sin t$, so the general solution is $X(t)=(\cos t)C + (\sin t) S$ for some matrices $C,S$.

The initial condition gives $C=I$, and the ODE gives $\dot{X}(t) = -(\sin t) I + (\cos t) S = (\cos t)A + (\sin t) AS$ from which we see that $S=A$.

Hence $X(t) = e^{At} = (\cos t)I + (\sin t) A$. Choosing $t=1$ gives the desired answer.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.